Development of high entropy alloy as catalyst for azo dye degradation in Fenton process - Hassan, N. H. A; Nasir, N.S.M; Rahman, S. N. A.; Irfan, A. R.; Nordin, Norhuda Hidayah (Polish Academy of Sciences, Institute of Metallurgy and Materials Science, 2023)
Azo dye is widely used in the textile industry since it is cost effective and simple to use. However, it becomes a continuous source of environmental pollution due to its carcinogenicity and toxicity. Various methods had been used to remove the azo dye in solution. One of the famous and frequently used is the Fenton process. The Fenton process is one of the advanced oxidation processes where iron catalysed hydrogen peroxide to generate hydroxyl radical. Treating azo dyes in solution requires a catalyst to enhance the process of degradation. Herein, high entropy alloys (HEAs) have been proposed as a catalytic material to enhance the performance of Fenton process for azo dye degradation. HEAs have been reported as a promising catalyst due to its high surface area. The higher the number of active sites, the higher the rate of azo dye degradation as more active sites are available for adsorption of azo dyes. The results have shown that HEAs can be used as a catalyst to fasten the Fenton reaction since the degradation time is proven to be shorter in the presence of HEAs. The method derived from the result of this study will contribute in treating azo dyes for wastewater management in the Fenton process.